2017
DOI: 10.1016/j.jpowsour.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coating density on oxidation resistance and Cr vaporization from solid oxide fuel cell interconnects

Abstract: Manganese cobalt spinel oxides are promising materials for protective coatings for solid oxide fuel cell (SOFC) interconnects. To achieve high density such coatings are often sintered in a two-step procedure, involving heat treatment first in reducing and then in oxidizing atmospheres. Sintering the coating inside the SOFC stack during heating would reduce production costs, but may 2 result in a lower coating density. The importance of coating density is here assessed by characterization of the oxidation kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 63 publications
6
74
1
Order By: Relevance
“…Uncoated Crofer 22 APU oxidized at 900 °C has a similar oxidation rate as reported by Huczkowski et al [37] (1×10 -12 g 2 cm -4 s -1 ). The oxidation rate of uncoated Crofer 22 APU at 800 °C is however somewhat lower than we have previously reported for the same alloy batch (4.2×10 -14 g 2 cm -4 s -1 [38]) and what was measured by Gavrilov et al [39] (5.6×10 -14 g 2 cm -4 s -1 ) and Molin et al [40] (2.84×10 -14 g 2 cm -4 s -1 ). This can be attributed to the pre-oxidation heat treatment (900 °C, N 2 -H 2 , 2 h and 800 °C, air, 2 h).…”
Section: Oxidation Kineticscontrasting
confidence: 61%
See 1 more Smart Citation
“…Uncoated Crofer 22 APU oxidized at 900 °C has a similar oxidation rate as reported by Huczkowski et al [37] (1×10 -12 g 2 cm -4 s -1 ). The oxidation rate of uncoated Crofer 22 APU at 800 °C is however somewhat lower than we have previously reported for the same alloy batch (4.2×10 -14 g 2 cm -4 s -1 [38]) and what was measured by Gavrilov et al [39] (5.6×10 -14 g 2 cm -4 s -1 ) and Molin et al [40] (2.84×10 -14 g 2 cm -4 s -1 ). This can be attributed to the pre-oxidation heat treatment (900 °C, N 2 -H 2 , 2 h and 800 °C, air, 2 h).…”
Section: Oxidation Kineticscontrasting
confidence: 61%
“…This can in part be attributed to differences in Cr evaporation from the coated and uncoated samples. We have previously shown that a MCFe coating reduces the Cr evaporation rate of Crofer 22 APU by a factor of 10-30 at 800 °C in air with 3 % H 2 O [38]. Decreasing the temperature from 800 °C to 700 °C is here shown to decrease the oxidation rate by a factor of 10, while the rate of Cr evaporation has been shown to decrease by only a factor of 2-3 in this temperature interval [41].…”
Section: Oxidation Kineticsmentioning
confidence: 51%
“…Materials based on MnCo 2 O 4 are interesting for a broad range of applications, from room temperature to high temperatures (800 • C). They can be used in Li-ion battery electrodes [6,7], electrochemical supercapacitors [8] and as coating materials for steel interconnects for fuel cells [9][10][11]. The microstructure and the composition of the spinel strongly affect its performance and applicability in a specific technology.…”
Section: Introductionmentioning
confidence: 99%
“…An effective solution is to coat the alloy surface with protective layers . Many different materials have been evaluated for a possible corrosion protection . Among the materials, Mn‐Co spinels have been proposed as being very effective in reducing chromium evaporation .…”
Section: Introductionmentioning
confidence: 99%